The Development of Non-Formal Technological and Vocational Education in Village Communities - Widaningsih, Lilis; Abdullah, Ade Gafar (INVOTEC, 2016)
This article presents a preliminary study which was done through a literature review of various scientific references on the development of human resources through non-formal technological and vocational education. Current issues and problems in developing countries are related to the low quality of human resources in villages due to the low education and skills (technological and vocational skills). The development of non-formal technological and vocational education for village communities becomes an alternative solution, particularly when formal education does not provide solutions. With the concept of life-long learning, non-formal technological and vocational education is based on practical knowledge and skills. Non-formal education allows a learning model which addresses individuals’ learning needs. Thus, it becomes one of solutions to overcome unemployment.